Engaging Strategies for Early Childhood Foreign Language Acquistion: A Systematic Literature Review - Surahmat, Zulkifli; Sukmawati, Henni; Tri Muliyana, Agnezia; Rahmaniar, Rahmaniar; Sahibu, Mutmainna; Sardi, Ahmed (JELITA, 2025)
The most appropriate period for learning a new language is considered the early childhood period, when children can learn languages easily and instinctively without, for instance, having to go through tedious textbooks. The objective of this review is to identify the best practices aimed at fostering foreign language acquisition by drawing upon previous empirical studies. The results indicate that the children's language skill development is greatly enhanced when the learning process is made fun through playful activities, and the singing and telling of stories. Structured approaches such as Total Physical Response (TPR), bilingual education, and even the active participation of the parents in the home language environment have been noted to foster language learning as well. Supporting early childhood learners and teachers with creativity and flexible instruction tailored to the rapidly growing characteristics of the children results in effective language acquisition, hence emerges as a key pillar on guiding principles towards successful language mastery. This review indicates that purposely designed instruction towards learners in their early years enhances teaching effectiveness yielding improved results while the use of active, direct, and fun-filled strategies yields better results in mastering languages.